2021
DOI: 10.3390/ijms22052285
|View full text |Cite
|
Sign up to set email alerts
|

Development of 18F-Labeled Radiotracers for PET Imaging of the Adenosine A2A Receptor: Synthesis, Radiolabeling and Preliminary Biological Evaluation

Abstract: The adenosine A2A receptor (A2AR) represents a potential therapeutic target for neurodegenerative diseases. Aiming at the development of a positron emission tomography (PET) radiotracer to monitor changes of receptor density and/or occupancy during the A2AR-tailored therapy, we designed a library of fluorinated analogs based on a recently published lead compound (PPY). Among those, the highly affine 4-fluorobenzyl derivate (PPY1; Ki(hA2AR) = 5.3 nM) and the 2-fluorobenzyl derivate (PPY2; Ki(hA2AR) = 2.1 nM) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…[ 18 F]­3 has a high affinity for A 2A R in vitro and can effectively penetrate the blood–brain barrier, but it also exhibits severe off-target in the brain and defluorination. Lai et al also modified the structure of high-affinity A 2A R therapeutics, such as tozadenant and PPY, aimed at synthesizing potential tracers with a stronger affinity for A 2A R receptors. , However, PET imaging revealed that such compounds had serious off-target imaging in the brain. , The possible explanation for off-target phenomenon may be that other targets have a higher affinity for these tracers than A 2A R or other targets have a lower affinity for tracers than A 2A R, but their content is much higher than A 2A R. From the experience of these failures, radiopharmaceuticals can efficiently validate the targeting specificity and selectivity of therapeutic drugs to improve the progress of drug research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 F]­3 has a high affinity for A 2A R in vitro and can effectively penetrate the blood–brain barrier, but it also exhibits severe off-target in the brain and defluorination. Lai et al also modified the structure of high-affinity A 2A R therapeutics, such as tozadenant and PPY, aimed at synthesizing potential tracers with a stronger affinity for A 2A R receptors. , However, PET imaging revealed that such compounds had serious off-target imaging in the brain. , The possible explanation for off-target phenomenon may be that other targets have a higher affinity for these tracers than A 2A R or other targets have a lower affinity for tracers than A 2A R, but their content is much higher than A 2A R. From the experience of these failures, radiopharmaceuticals can efficiently validate the targeting specificity and selectivity of therapeutic drugs to improve the progress of drug research.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 However, PET imaging revealed that such compounds had serious off-target imaging in the brain. 37,38 The possible explanation for off-target phenomenon may be that other targets have a higher affinity for these tracers than A 2A R or other targets have a lower affinity for tracers than A 2A R, but their content is much higher than A 2A R. From the experience of these failures, radiopharmaceuticals can efficiently validate the targeting specificity and selectivity of therapeutic drugs to improve the progress of drug research.…”
Section: Micropet-ct Imaging Of Tmcaomentioning
confidence: 99%
“…Among the nine compounds, only the F-substituted 6-and 7-azaindoles bound σ 1 receptors with an affinity low enough (K i values > 500 nM) to exclude confounding binding in imaging studies performed at low-to sub-nanomolar concentration of the radiotracer. To finally select the best derivative for radiofluorination, we calculated the σ 2 :σ 1 selectivity values and identified RM273 (41) as the most suitable one with a ratio of about 400.…”
Section: Automated Radiosynthesis Of [ 18 F]rm273mentioning
confidence: 99%
“…For this purpose, the boronic acid pinacol ester precursor 45 was synthesized in one step from the corresponding bromo-derivative 44 via the Miyaura borylation reaction in high yield (>85%) as shown in Scheme 2 [40]. As described previously [34,39] and based on our own work [41] on the coppermediated radiofluorination of aryl boronic acid pinacol esters, manual radiosynthesis of [ 18 F]RM273 (Scheme 2) was performed initially to check if the reaction conditions usually applied for this kind of radiofluorination (e.g., [ 18 F]TBAF system in DMA and tBuOH as solvents) would give reasonable yields for further translation to an automated radiosynthesis module. Radiochemical yields of about 50% (calculated from the crude reaction mixture, non-decay-corrected) were obtained using the pinalcol precursor 45 and Cu(OTf) 2 (py) 4 at a molar ratio of approximately 1:4, and no further optimization was carried out.…”
Section: Automated Radiosynthesis Of [ 18 F]rm273mentioning
confidence: 99%
“…There is a notion that overstimulation of D2 receptors could be accountable for schizophrenia-positive symptoms. Scientists further found out that levodopa, a DA precursor, and amphetamine, a DA-releasing agent, worsened the symptoms of schizophrenia [1,4,5,[8][9][10][11][12][13][14][15][16]. Neuroimaging studies have revealed that schizophrenic patients display an escalated release of DA in the ventral striatum after amphetamine induction, indicating heightened sensitivity of their dopaminergic system when compared with a control group.…”
Section: Introductionmentioning
confidence: 99%